DoseCal: a virtual calculator for dosage conversion between human and different animal species. (4th March 2022) - Janhavi, P.; Divyashree, S.; Sanjailal, K. P.; Muthukumar, S. P.
Abstract: Context: The scientists as well as pharmacologists frequently convert the dose of drugs or extracts between human and different animal species. According to the literature, the extrapolation of the dose by simple conversion based only on body weight is not an accurate method. The miscalculation of dosage conversion may result in adverse effects due to overdose or reduced potency due to underdose. Aim: To develop a conversion calculator with factual factor like K m factor. Method: The virtual calculator was developed as a web-based application using hypertext pre-processor programming language. My SQL software was used to store the data related to DoseCal. Results: Based on the K m factor, dose conversion calculator called DoseCal was developed. The DoseCal would provide the dosage for both per kg and actual weight of the animal taken for the experiment. Conclusion: The DoseCal would assist scientists in the dosage conversion easily and accurately between species.